(untitled) (Annals of Medical Research, 2023)
Aim: This retrospective study aimed to determine the incidence of random findings in digital panoramic images acquired from edentulous patients presenting for conventional prosthetic rehabilitations or implant-supported dentures. Materials and Methods: In this retrospective study, of the patients aged 16 years and older, 950 of 1,100 panoramic films were evaluated by two maxillofacial radiologists (MA and IBY) in ambient light on an LCD monitor. The final classification and radiographic status of each finding were recorded after inter-observer consensus. Radiographs with low image quality and artifacts that did not include the demographic information of the patients were not included in the study. In the present study; impacted teeth, root remnants, radiolucent (RL) lesions, radiopaque (RO) lesions (including idiopathic osteosclerosis), foreign bodies, crest atrophies, soft tissue calcifications, maxillary sinus opacities, and Stafne bone defects were examined. Lesions affecting the alveolar region were divided into three regions as anterior (incisors and canines region), premolars and molars region. Results: Tonsillitis was observed in a total of 55 individuals, 26 men and 29 women. Sialolith was seen in a total of 3 patients, 2 male and 1 female, but phleboliths were not found in any of them. Styloid ligament ossification(SLO) was seen in a total of 125 patients, 69 of these cases were female and 56 were male, however calcified atherosclerotic plaque is the most common calcification with 156 individuals and a rate of 16.4% among calcifications. Laryngeal cartilage calcification, which is seen in 36 female and 23 male individuals. Conclusion: The outcome of this study indicated that the ratio of advantageous findings fixed in digital panoramic images of totally edentulous patients was highly rated. There are indispensable for patients with total edentulism such as routine use and careful examination of panoramic images.